7
$\begingroup$

Show the correctness of the equality by making use of the Cauchy product of the series $\cos(x)=\sum_{n=0}^{\infty}(-1)^n.\frac{x^{2n}}{(2n)!}$ and $\sin(x)=\sum_{n=0}^{\infty}(-1)^n.\frac{x^{2n+1}}{(2n+1)!}$. I've reached $$\cos(x).\cos(y)=\sum_{n=0}^{\infty}(-1)^n.\sum_{k=0}^{n}\frac{1}{(2k)!(2(n-k))!}.x^{2k}.y^{2(n-k)}$$ and $$\sin(x).\sin(y)=\sum_{n=0}^{\infty}(-1)^n.\sum_{k=0}^{n}\frac{1}{(2k+1)!(2(n-k)+1)!}.x^{2k+1}.y^{2(n-k)+1}$$ and $$\cos(x+y)=\sum_{n=0}^{\infty}(-1)^n.\sum_{k=0}^{2n}\frac{1}{k!(2n-k)!}.x^{k}.y^{2n-k}$$

but I guess I'm missing some steps or got something wrong.

$\endgroup$
4
$\begingroup$

Everything is fine so far. We can start from \begin{align*} \cos(x)\cos(y)&=\sum_{n=0}^\infty (-1)^n\sum_{k=0}^n\frac{x^{2k}y^{2n-2k}}{(2k)!(2n-2k)!}\tag{1}\\ \sin(x)\sin(y)&=\sum_{n=0}^\infty (-1)^n\sum_{k=0}^n\frac{x^{2k+1}y^{2n-2k+1}}{(2k+1)!(2n-2k+1)!}\tag{2}\\ \cos(x+y)&=\sum_{n=0}^\infty (-1)^n\sum_{k=0}^{2n}\frac{x^{k}y^{2n-k}}{k!(2n-k)!}\\ \end{align*}

We obtain \begin{align*} \cos(x+y)&=\sum_{n=0}^\infty (-1)^n\sum_{k=0}^{2n}\frac{x^{k}y^{2n-k}}{k!(2n-k)!}\tag{3}\\ &=\sum_{n=0}^\infty (-1)^n\sum_{k=0}^{n}\frac{x^{2k}y^{2n-2k}}{(2k)!(2n-2k)!}\\ &\qquad\qquad +\sum_{n=1}^\infty (-1)^n\sum_{k=0}^{n-1}\frac{x^{2k+1}y^{2n-2k-1}}{(2k+1)!(2n-2k-1)!}\tag{4}\\ &=\cos(x)\cos(y)+\sum_{n=0}^\infty (-1)^{n+1}\sum_{k=0}^{n}\frac{x^{2k+1}y^{2n-2k+1}}{(2k+1)!(2n-2k+1)!}\tag{5}\\ &=\cos(x)\cos(y)-\sin(x)\sin(y) \end{align*} and the claim follows.

Comment:

  • In (3) we split the inner sum in even and odd parts. We do so by replacing $k\rightarrow 2k$ and $k\rightarrow 2k+1$.

  • In (4) we see the left-hand series is already $\cos(x)\cos(y)$ according to (1). We shift the index $n$ of the right-hand series by one to start from $n=0$.

  • In (5) we see the right-hand series is $-\sin(x)\sin(y)$ according to (2).

$\endgroup$
2
  • $\begingroup$ The splitting trick is quite useful! I just want to point out a typo in (4) and (5): the factorial in the denominator should be $(2k+1)!$, not $(2k-1)!$. $\endgroup$ Dec 7 '16 at 17:37
  • 1
    $\begingroup$ @HaidarAbboud: Typo corrected. Thanks for the hint! $\endgroup$
    – epi163sqrt
    Dec 7 '16 at 17:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.